Plan de negocio para la creación de una empresa de capacitación ambiental para las instituciones educativas en la ciudad de Bogotá (2021)
In this business plan, it consists of teaching and training students in the schools of the city of Bogotá through dynamic methodologies to learn to take care of the environment, from an early age, from primary and secondary school. Allowing the student to make changes in their habits and customs in which they are also developing.